Identification Of Infant Mortality Rate Factors Using Spatial Autoregressive Moving Average - Cahyoko, Fajar Dwi; Subratha, Hesteria Friska Armynia (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2024)
Introduction: Infant mortality rate (IMR) is one of the indicator of the success for maternal and child health programs. Infant mortality rates affected by biological, environmental, socioeconomic factors and quality of healthcare services. This study aimed to analyze the factors affecting infant mortality rates in the East Java Province using a spatial regression model.Methods: The research units were all 38 districts and cities in East Java Province. Secondary data from the 2023’ Health Profile of East Java Province was used in this study, which included the number of infant deaths and the biological, environmental, socioeconomic factors, the availability and quality of health services. In this study, spatial modelling was conducted using an area approach and spatial influence using the Spatial Autoregressive Moving Average (SARMA) method with Queen Contiguity spatial weights.Results: Based on R2 and AIC values, the Spatial Autoregressive model was preferable to Ordinary Least Squares. The obtained model showed that low birth weight and the percentage of the population that can access good sanitation were the significant factors influencing infant mortality in this study. The other factors: percentage of deliveries by health workers, obstetric complications handled, percentage of poor people, infants receiving vitamin A, and infants receiving exclusive breastfeeding had no significant effect on Infant Mortality Rates.Conclusion: Factors that had significant effect on infant mortality rates in this study were low birth weight and percentage of residents who had access to proper sanitation.